2002
DOI: 10.1159/000068358
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Oxygen Supplementation on the Arterial Ketone Body Ratio in Human Cirrhosis

Abstract: Background/Aims: Data from studies in experimental models have suggested that the impairment of mitochondrial function and altered redox state that occur in cirrhosis may be due to impaired hepatic oxygenation. Since interventions that improve oxygen delivery to hepatocytes may improve mitochondrial functions, we studied the effects of oxygen supplementation on the arterial ketone body ratio (AKBR) in normal volunteers and patients with cirrhosis. Methods: After a 2-hour fast, ketone bodies were measured in ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…It has been reported that hepatocellular hypoxemia directly contributes to the progression of liver fi brosis, 9 and also to liver regeneration failure in cirrhotic livers. 10 Froomes et al 11 measured the arterial ketone body ratio (AKBR; acetoacetate/3-hydroxybutyrate) in patients with cirrhosis to investigate hepatic mitochondrial function. 12 Their results revealed that low AKBR levels in such patients were signifi cantly increased after they received 2 h of oxygen supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that hepatocellular hypoxemia directly contributes to the progression of liver fi brosis, 9 and also to liver regeneration failure in cirrhotic livers. 10 Froomes et al 11 measured the arterial ketone body ratio (AKBR; acetoacetate/3-hydroxybutyrate) in patients with cirrhosis to investigate hepatic mitochondrial function. 12 Their results revealed that low AKBR levels in such patients were signifi cantly increased after they received 2 h of oxygen supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have for the first time looked in detail into regional variations in the concentrations of ketone bodies in cirrhosis and in patients suffering from a common complication of cirrhosis, hepatic encephalopathy. Previous studies have shown that the arterial ketone body ratios are different from controls in patients with various liver diseases (7–10). It is lower in patients with cirrhosis but it can be improved in a state of improved oxygenation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have described a relationship between the blood ketone body ratio (acetoacetate/β‐hydroxybutyrate) as a marker of the hepatic energy charge (5–7). As β‐hydroxybutyrate is produced from acetoacetate with the consumption of NADH, their ratio accurately reflects the ratio of free NAD to reduced NADH (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…jedoch kontrovers diskutiert, da ebenso Studien existieren, die keinen prognostischen Wert dieses Tests zeigen[19] und des Weiteren der Test scheinbar durch Sauerstoffgabe beeinflusst wird[13].Auch wenn verschiedene Untersucher Leberfunktionsteste in die Operationsplanung bezüglich des Ausmaßes der Operation bzw. der Operationstechnik integriert haben[49,63,64], so bleibt es jedoch unwahrscheinlich, dass ein einzelner Leberfunktionstest ausreichend ist, um Patienten mit postoperativen Leberversagen von Patienten zu unterscheiden, die eine Leberteilresektion problemlos überstehen.…”
unclassified